FREQUENCY OF BODY-FOCUSED REPETITIVE BEHAVIOURS IN MEDICAL STUDENTS OF PESHAWAR - Khan, Shifa A.; Khan, Mahd Aftab; Khan, Mahnoor; Sethi, Mifrah Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2018)
Objective: To find out the frequency of body-focused repetitive behaviours (BFRBs) in medical students of Peshawar. Methodology: This cross-sectional study included students from different medical colleges of Peshawar. Habit questionnaire was used to check the common habits; it consists of 11 questions with a simple "˜Yes' or "˜No' responses and noting the feelings before, during and after committing the behaviour. The Cronbach's alpha reliability of Habit questionnaire in our study was 0.88. SPSS v.20 was used to analyze the data and a p value of <0.05 was considered significant for results when tests of significance were applied. Results: The mean age of the sample (n=549) was 20.7 ±1.5 years with majority were male students (n=285, 51.9%) and from private sector (n=432, 78.7%). The most common habit in medical students was chewing lips (n=365, 66.5%). The most common feeling associated before and during committing these habits was irritability [(n=84, 15.3%) and (n=99, 18%)] while it was calmness, after committing the habits (n=121, 22%). The gender wise comparison showed that statistically significant habit in male was punching a wall (p= 0.000) and in females, it was chewing lips (p= 0.024). Similarly students of public sector had significantly more involvement in the habits of biting nails, chewing lips, clinching/ grinding teeth, scratching/picking skin, pulling hair on head and eyebrows/ lashes and punching wall, as compared to private sector (p <0.05). Conclusion: There was a high frequency of body-focused repetitive behaviours in medical students. Significantly more common habit in females was chewing lips while in males, it was punching the wall.